2021
DOI: 10.18632/aging.203107
|View full text |Cite
|
Sign up to set email alerts
|

Propofol ameliorates renal ischemia/reperfusion injury by enhancing macrophage M2 polarization through PPARγ/STAT3 signaling

Abstract: Propofol (Pro) confers protection against renal ischemia/reperfusion (rI/R) injury through incompletely characterized mechanisms. Since Pro has shown net anti-inflammatory properties as part of its beneficial effects, we examined the potential role of Pro in the modulation of macrophage polarization status during both rI/R injury in vivo and exposure of cultured peritoneal macrophages (PMs) to hypoxia/reoxygenation (H/R). Rats were subjected to 45-min r/IR surgery or a sham procedure and administered PBS (vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Many studies have confirmed the effect of drugs or molecular compounds on kidney IRIs. For example, propofol can enhance the polarization of macrophage M2 through the PPARγ/STAT3 signaling pathway and alleviate RIRIs ( 36 ); traprostalitib reduces mitochondrial damage during RIRIs in rats ( 37 ); dexmedetomidine may relieve RIRIs by suppressing the inflammatory responses ( 38 ). These drugs or molecular compounds may be potential drugs for the future treatment of RIRIs.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed the effect of drugs or molecular compounds on kidney IRIs. For example, propofol can enhance the polarization of macrophage M2 through the PPARγ/STAT3 signaling pathway and alleviate RIRIs ( 36 ); traprostalitib reduces mitochondrial damage during RIRIs in rats ( 37 ); dexmedetomidine may relieve RIRIs by suppressing the inflammatory responses ( 38 ). These drugs or molecular compounds may be potential drugs for the future treatment of RIRIs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, PIAS3, known as protein inhibitor of activated STAT3, could block the DNA-binding activity of STAT3 and inhibit STAT3-mediated gene expression ( Chung et al, 1997 ). Moreover, the expression of STAT3 could be modulated by transcription factors such as PPARγ, Src and SMAD3, or microRNAs (miRNAs) such as miR-125a-5p and miR-519a ( Xiao et al, 2017 ; Li et al, 2018 ; Xu et al, 2018 ; Liu et al, 2021 ; Zhang et al, 2021 ). In addition, some small molecules such as SD-36 could degrade STAT3 to disrupt its biological function ( Bai et al, 2019 ; Zhou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be that propofol does not alter the anti-inflammatory or tissue repair functions of M2 macrophages ( Kochiyama et al, 2019 ). However, a recent study suggested that propofol improved renal ischemia-reperfusion injury by inducing the expression of the M2 polarization marker via the PPARγ/STAT3 pathway ( Liu et al, 2021b ). The pathways and effect of propofol on the polarization of macrophages are shown in Figure 3 .…”
Section: Propofol Regulation Of Macrophage Activation and Functionmentioning
confidence: 99%
“…Notably, many clinical and preclinical studies showed that propofol reduced ischemic damage to vital organs, such as the heart ( Nederlof et al, 2017 ), brain ( Sousa et al, 2021 ), kidney ( Liu et al, 2021b ), and lung ( Sousa et al, 2021 ). Propofol reduced CD45 + and increased vascular cell adhesion molecule (VCAM)-1 in the ischemic stroke model, but it did not protect the brain or lung in experimental acute ischemic stroke.…”
Section: Propofol Regulation Of Macrophage Activation and Functionmentioning
confidence: 99%
See 1 more Smart Citation